ANALISIS PENERAPAN INOVASI ICE BREAKING DALAM PENGELOLAAN PESERTA DIDIK DI SDN 02 TAROGONG - Intan Sari, Yusi; Aulia Rahman, Maulida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the problem of learning boredom and low student participation in the learning process at elementary schools, particularly at SDN 02 Tarogong. This condition has an impact on decreasing learning motivation, lack of concentration, and low student involvement in classroom learning activities. Learning practices that are still conventional and monotonous become one of the main factors causing students to easily lose focus and interest during the learning process in the classroom. In addition, less varied teaching methods make the classroom atmosphere less engaging for students. Therefore, learning innovation is needed to create a more enjoyable and interactive learning environment and to optimally increase student activeness in every learning activity carried out by the teacher in the classroom. This study aims to analyze the implementation of ice breaking innovation in student management and to examine its impact on students’ motivation and participation in learning. This research uses a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The research subjects consist of teachers and students at SDN 02 Tarogong. Data analysis is conducted inductively through the stages of data reduction, data display, and conclusion drawing, and its validity is tested using source and method triangulation techniques in this qualitative research. The results show that the structured and well-planned implementation of ice breaking can reduce student boredom, increase learning motivation, and encourage active participation in the classroom significantly. Activities such as group games, simple physical activities, and puzzles are proven effective in creating a more interactive and enjoyable classroom atmosphere, as well as supporting an optimal, effective, and sustainable learning process for students comprehensively and consistently.